The Japanese economy : recent trends and outlook / 1998 ([Tokyo] : Coordination Bureau, Economic Planning Agency, Japanese Government, 1998)
The books contains the whole text of the official economic outlook, which elaborates under what policy environment the continuation of recovery is expected and how the configuration of main economic indicators should look like with some useful figures, tables and materials as a supplement to the official outlook.
Title from cover.
opc 20/12/16
Loans
Keywords: Economic forecasting; Economic indicators; Economic conditions; Japan